µCT scanning effects on aDNA and a multi-step workflow for archaeological petrous portions - Lumila Paula Menéndez; Pierre Luisi; María Clara López-Sosa; Sergio Monteiro Da Silva; Laura T. Buck; Susan C. Kuzminsky; Mirsha Quinto Sánchez; Anne Le Maître; Christine Chappard; Cassandra Rios; Hans Groh; Wara Siles; et al. (PLoS ONE, 2026)
The petrous portion of the temporal bone (often informally referred to as the “petrous bone”) is a key element in human evolutionary studies due to its exceptional preservation of biomolecules and morphological information. Intensive and often redundant sampling raises concerns about sustainability and long-term conservation, however. Digital recording of morphology (micro-computed and medical tomography) can preserve what destructive sampling destroys, enabling future analyses, yet there have been concerns regarding its effect on biomolecular preservation. Here, we present a systematic observational assessment of whether micro-computed tomography (µCT)—a widely used tool for digital preservation—affects ancient DNA (aDNA) integrity in archaeological human petrous portions. We analyzed 93 archaeological samples from Argentina, of which 50 were µCT-scanned prior to molecular analysis and 43 were not. We compared six commonly used molecular parameters, including endogenous DNA content, read length, cytosine deamination patterns, and mitochondrial and nuclear contamination estimates. No statistically significant differences were observed between scanned and unscanned samples across these parameters (Mann-Whitney/Wilcoxon tests, p > 0.05). Although mitochondrial contamination estimates were marginally higher in scanned samples ( p = 0.051), they largely remain below the widely accepted 5% threshold for genomic analysis. Moreover, this pattern was not observed when considering nuclear contamination. Within the limits of this non-paired design, these results suggest that µCT imaging, under the scanning parameters applied here, does not introduce large or systematic bias derived from disruptions in standard aDNA preservation metrics. Building on these observations and on our collaborative experience with the shared use of archaeological samples across complementary research lines, and given that our results show that µCT imaging under appropriate scanning conditions does not significantly compromise DNA preservation, we propose a sustainable, multi-step workflow that integrates biological profiling, osteobiography, imaging, and compositional pre-screening prior to molecular sampling. This approach aims to maximize the scientific information obtained from skeletal collections while minimizing destructive practices, thereby promoting ethical and sustainable research on irreplaceable anthropological remains, and fostering interdisciplinary collaboration.